Inherently Stealthy and Highly Tumor-Selective Gold Nanoraspberries for Photothermal Cancer Therapy - Gandra, Naveen (Sci Rep, 2015)
Owing to their unique optical properties such as large absorption and scattering cross section and large enhancement of electromagnetic field at the surface, plasmonic nanostructures have received extensive attention as a highly promising class of materials for nano-oncology. Most of the existing plasmonic nanostructures require extensive post-synthesis treatments and biofunctionalization routines to mitigate their cytotoxicity and/or make them tumor-specific. Here, we report one-pot synthesis of a novel class of plasmonic nanostructures, namely, gold nanoraspberries (GRBs) with tunable size and localized surface plasmon resonance by using a naturally abundant polysaccharide, chitosan, which acts as a template and capping agent. Significantly, the GRBs, which do not require any further biofunctionalization, exhibit excellent selectivity to tumor cells, thus enabling locoregional therapy at the cellular level. We demonstrate the tumor-selectivity of GRBs by photothermal ablation of tumor cells selectively from their co-culture with normal cells. The simple, scalable and tumor-selective nature of GRBs makes them excellent candidates for translational plasmonics-based nanomedicine.